Characterization of favorable lithofacies in tight sandstone reservoirs and its significance for gas exploration and exploitation: A case study of the 2nd Member of Triassic Xujiahe Formation in the Xinchang area, Sichuan Basin - LIU, Junlong; LIU, Zhongqun; XIAO, Kaihua; HUANG, Yanqing; JIN, Wujun (Petroleum exploration and development, 2020)
By using core, logging curves, and experiment data, favorable lithofacies types in the 2nd Member of Triassic Xujiahe Formation in the Xinchang area, Sichuan Basin were classified, standard of the favorable lithofacies was established, planar distribution regularities of the favorable lithofacies were identified, and forming mechanisms of the favorable lithofacies and their control effect on production were examined. (1) The 2nd Member of Xujiahe Formation has twelve types of lithofacies, among which multiple layer medium-coarse grain sandstone lithofacies, parallel bedding medium-coarse grain sandstone lithofacies, massive bedding medium-coarse grain sandstone lithofacies, inclined bedding medium-coarse grain sandstone lithofacies, and charcoal-bearing medium-coarse grain sandstone lithofacies with better physical properties and higher gas content are favorable lithofacies; they feature low gamma, low neutron porosity, low resistivity, and high acoustic travel time on logging curves. (2) The sedimentary process controls spatial distribution of sand bodies which are the material basis of the favorable lithofacies; post diagenetic fluids would differentially reconstruct the favorable lithofacies; tectonic activities and abnormal formation pressure made strata slide along the weakness plane, giving rise to fractures in different types of rocks, which can enhance the reservoir permeability significantly. (3) The development degree of favorable lithofacies is a major factor affecting stable production of gas well.